(untitled) (Journal of actual problems of jurisprudence, 2018)
In the article the acquittal – a form of judicial review of the legality and protection of human rights in pre-trial proceedings. The author shows the importance and significance of acquittals as a factor confirming the operating principle of the presumption of innocence in criminal proceedings. Comparing the situation of the accused and the victim the author believes that it is necessary to make some improvements in the procedural position of the victim. Key words: verdict of acquittal, the presumption of innocence, defense, prosecution, probation, court supervision.